1963
DOI: 10.1063/1.1718559
|View full text |Cite
|
Sign up to set email alerts
|

Very Large Boron Trifluoride Proportional Counters

Abstract: More than 50 very large BF3 counters, each approximately 6 ft (180 cm) long and 6 in. (15 cm) in diameter have been made for cosmic-ray monitors. During the fabrication of these counters, the characteristics at varying gas pressures have been studied and the alpha backgrounds of the various metals used for cathodes have been determined. The counters have excellent characteristics at pressures up to 30 cm Hg and perfectly acceptable characteristics to 60 cm Hg pressure. With anode diameter 0.008 in. (0.2 mm) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…The resulting count rate was 50 per minute, but pulse height analysis indicated that these counts were still predominantly due to neutrons. This is consistent with the finding of Fowler [1963] that the typical background due specifically to alpha particles from radionuclides in the detector itself is about 5 per minute. In the Pole monitor at solar minimum (1997 epoch), the count rate of this detector would be about 6400 per minute per tube, so background is at the 0.8% level at worst (and probably much less), which is not enough to impact our conclusions.…”
Section: Could the South Pole Decline Be Instrumental?supporting
confidence: 92%
“…The resulting count rate was 50 per minute, but pulse height analysis indicated that these counts were still predominantly due to neutrons. This is consistent with the finding of Fowler [1963] that the typical background due specifically to alpha particles from radionuclides in the detector itself is about 5 per minute. In the Pole monitor at solar minimum (1997 epoch), the count rate of this detector would be about 6400 per minute per tube, so background is at the 0.8% level at worst (and probably much less), which is not enough to impact our conclusions.…”
Section: Could the South Pole Decline Be Instrumental?supporting
confidence: 92%
“…The branching ratio is obtained by taking ratio of the sums of the number of pulses in the 2.78 MeV peak to the total number of pulses collected. The value obtained is 6.1 ± 0.2, which agrees with values reported in the literature [1,4]. Figure 2 shows gas gain as a function of applied anode voltage for detectors filled with pure BF 3 and BF 3 + Ar mixture.…”
Section: Methodssupporting
confidence: 90%
“…But BF 3 is not an ideal proportional counter gas. Worsening of plateau characteristics results with increase in cathode diameter and it is not possible to obtain good characteristics in counters with gas filled at 60 cm Hg and diameters more than 3.8 cm [1,2]. This may be due to fluctuations of the number of initial ion pairs produced due to wall effects and fluctuation of the gas amplification due to electron capture by the impurities in the gas or to saturation effects because of the space charge at the anode wire [3].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…BCl 3 is of great importance in chemical physics due to their nonpolar and highly plane symmetric (D 3h ) geometry. For this reason, BCl 3 is extensively used in deposition and doping of boron [22].…”
Section: B-aln Thin Film Synthesismentioning
confidence: 99%